2023
DOI: 10.3390/antiox12040941
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Vitamin C in Women with Prenatal Depression and Anxiety: Effect of Multinutrient Supplementation

Abstract: Elevated inflammation has been associated with adverse mood states, such as depression and anxiety, and antioxidant nutrients, such as vitamin C, have been associated with decreased inflammation and improved mood. In the current study comprising a cohort of pregnant women with depression and anxiety, we hypothesised that elevated inflammation would be associated with adverse mood states and inversely associated with vitamin C status and that multinutrient supplementation would optimise vitamin concentrations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Other studies reported that vitamin C supplementation or intake significantly reduced CRP levels in various subgroups such as males, non-smokers, healthy subjects, younger people, and at doses <500 mg/day (32). Some studies also found an inverse connection between CRP and vitamin C levels in special populations such as pregnant women with depression and anxiety (33) and patients with septic cardiomyopathy (34).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported that vitamin C supplementation or intake significantly reduced CRP levels in various subgroups such as males, non-smokers, healthy subjects, younger people, and at doses <500 mg/day (32). Some studies also found an inverse connection between CRP and vitamin C levels in special populations such as pregnant women with depression and anxiety (33) and patients with septic cardiomyopathy (34).…”
Section: Discussionmentioning
confidence: 99%